The Effect of Psychodrama on Women’s Codependence, Self-Realization and Problem Solving Skill Perception - Ulusoy, Yağmur; Kırlangıç Şimşek, Bircan (Journal of History Culture and Art Research, 2021)
The aim of the present study was to investigate the impact of psychodrama on the codependency, self-actualization and problem-solving skills of women attending Public Education Center Tailoring Courses. The study was conducted with the quasi-experimental design based on the pretest-posttest model with an experimental group. Fifteen volunteering women attending tailoring courses at Malatya Battalgazi District Public Education Center during the 2015-2016 academic year participated in the study. The study data were collected with the Composite Codependency Scale, Health-Promoting Lifestyle Profile, and Problem-Solving Inventory. These three scales were applied to the study group before the application. After the pre-test, a psychodrama group study that included 18 sessions was conducted with eight women in the study group. At the end of the application, the scales were applied as post-test measurements to the study group. To test the effectiveness of the experimental process, the dependent samples t test technique was used. The comparison of the study group pretest and posttest scores revealed a significant difference between pretest and posttest self-actualization scores; however, there was no significant difference between codependency, interpersonal control, self-sacrifice, suppression of emotions, and problem-solving skill perception pretest and posttest scores. Thus, it was observed that psychodrama had a significant effect on the improvement of the self-actualization levels of participating women; however, it did not have a significant effect on the reduction of their negative perceptions about problem-solving skills and codependency levels.